Royal palm nut meal for fattening pigs. Influence of body weight on rectal digestibility and faecal output of materials - Ly, Julio; Reyes, J.; Delgado, E.; Ayala, L?zara; Castro, Manuel Jos? (Cuban Journal of Agricultural Science, 2013)
A 2 x 3 factorial arrangement was applied to measure rectal digestibility of nutrients and faecal output of materials, at the starting and finishing fattening stages (30 and 80 kg). Twenty four castrated Cuban Criollo x CC21 male pigs were used. Animals were fed ad libitum for 14 weeks with final molasses alone (80 %) or with raw sugar or ground royal palm nut (45 %). The body weight x diet interaction was significant (P < 0.05) for raw fiber digestibility, NDF and N, but not for DM and organic matter at rectal level. Final molasses and sugar made to decrease rectal digestibility with weight increase, while with royal palm nut the opposite occurred. In general, rectal digestibility of nutrients was significantly higher (P < 0.001) with sugar and lower with royal palm nut. Faecal output of materials was considerably low in animals fed the raw sugar contained in the diet. The inverse happened with the royal palm nut. If royal palm nut constitutes a substantial part of low protein diets for pigs, rich in sugar cane molasses, this local feeding source could raise the digestive indices during fattening. Key words: pigs, rectal digestibility, body weight, molasses, royal palm nut